2016
DOI: 10.1001/jamaoto.2016.2807
|View full text |Cite
|
Sign up to set email alerts
|

Association of Clinical Risk Factors and Postoperative Complications With Unplanned Hospital Readmission After Head and Neck Cancer Surgery

Abstract: This study evaluated clinical factors and postoperative complications to determine which ones were associated with 30-day unplanned hospital readmission among patients undergoing surgery for malignant tumors of the head and neck. Further understanding of which complications are associated with unplanned readmission after head and neck surgery will allow for improved risk stratification and development of postoperative care protocols to reduce unplanned hospital readmission.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
84
1

Year Published

2017
2017
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(97 citation statements)
references
References 26 publications
12
84
1
Order By: Relevance
“…Our findings of high rates of readmission after TORS for OPSCC expand on the work of previous authors who have studied readmission after otolaryngologic surgery (3.1%‐9.5%) . The results presented are similar to recent estimates for readmission following all surgery for head and neck cancer as a group (5.1%‐16.1%) . A nationwide study focusing on TORS for OPSCC estimated readmission rates between 3.1% and 6.1% but was limited by only including the index hospital as a site of readmission .…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Our findings of high rates of readmission after TORS for OPSCC expand on the work of previous authors who have studied readmission after otolaryngologic surgery (3.1%‐9.5%) . The results presented are similar to recent estimates for readmission following all surgery for head and neck cancer as a group (5.1%‐16.1%) . A nationwide study focusing on TORS for OPSCC estimated readmission rates between 3.1% and 6.1% but was limited by only including the index hospital as a site of readmission .…”
Section: Discussionsupporting
confidence: 86%
“…This reinforces the notion that proper discharge planning and patient counseling regarding hemorrhage around the time of discharge are of the utmost importance to prevent hemorrhage‐associated morbidity. Past studies of readmissions following surgery for head and neck cancer consistently reported wound complications to be the predominant factor associated with readmission; however, in our dataset only 15 (12.8%) readmissions were related to wound complications, infection, or sepsis . This further emphasizes the fact that TORS patients make up a unique group.…”
Section: Discussioncontrasting
confidence: 60%
“…Several other studies have examined readmission rates in the larger head and neck oncology population. Bur et al used the NSQIP database to review 7605 patients who underwent various procedures for head and neck cancer and found a 5.1% readmission rate within 30 days postoperatively . Free flap procedures were excluded, 48% were outpatient procedures, and 49% of surgeries were classified as clean.…”
Section: Discussionmentioning
confidence: 99%
“…The reported 30‐day readmission rates in patients undergoing surgery for head and neck cancer range from 5.1% to 26.5% . This broad range primarily reflects the different methodology and inclusion criteria used for various studies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation